Aleitamento materno em prematuros: conhecimentos e caracterização sócio-demográfica de um grupo de mães - Arroyo, Marta Alves Silva (2007)
The benefits of breast feeding both for the mother and for the child, as well as the harm caused by the lack of it or the early weaning are largely divulged by the literature. In Brazil the rates of breast feeding are low for the population in general and mainly in the case of prematurity due to the very characteristics of mothers and of prematures. This work aimed at characterizing mothers of newborns and prematures identifying their knowledge about breast feeding. Casuistic and method: The study has been approved by the Ethics Committee. Research a 104 mothers who had their deliveries at Hospital de Base in Sao Jose do Rio Preto, and who fulfilled the inclusion criteria and who were characterized under the sociodemografic variables, gestation and delivery data, general aspects, general and specific knowledge about breast feeding under normal and prematurity conditions were researched from March to April, 2002. Results: Sample of 80 mothers of newborns infants being group I and 24 mothers premature infants being group II, who were young, poorly educated, with low income without professional occupation. Caesareans were prevalent in group I and normal delivery in group II, but with high rate of caesarians in both groups. Neither mothers from group I nor from group II planned their pregnancy, but carried out the prenatal in time. Concerning the general aspects of breast feeding, despite the fact that most mothers did not receive information, they are willing to breast feed and can manage to do it. Mothers from both groups show superficial knowledge about the benefits of breast feeding for the mother-child health, for when questioned in depth they contradict the pointed knowledge, also they lack of knowledge on how to handle breast feeding in prematurity situation. Conclusion: Both groups presented similar characterization showing the need of intervention and of support just after delivery and follow-up of hospital discharge.